"Green et al. Paranoid Thoughts Scale": French validation and development of a brief version. (March 2021) - Bianchi, Renzo; Verkuilen, Jay
Abstract: The "Green et al . Paranoid Thoughts Scale" (GPTS) has become a popular measure in paranoia research. The GPTS assesses paranoid ideation based on ideas of reference and persecution. The purpose of this study was twofold. First, we examined the characteristics of the French-translated GPTS. More specifically, we investigated the psychometric and structural properties of the GPTS in its original, 32-item version and its revised, 18-item version. Second, we developed a briefer, 8-item version of the scale (GPTS-8). We relied on a nonclinical sample of 503 individuals. We relied on confirmatory factor analysis (CFA), exploratory structural equation modeling (ESEM) bifactor analysis, Mokken scaling, and the DETECT multidimensionality index. Two-factor CFA models exhibited a satisfactory fit with all versions of the GPTS. Between-factor correlations, however, were very large. ESEM bifactor analysis suggested that all versions of the GPTS were essentially unidimensional. The GPTS-8 demonstrated strong reliability and high factorial validity. Although the DETECT index suggested that some degree of multidimensionality could not be excluded, Mokken scaling confirmed that the GPTS-8 can be considered unidimensional in practice. This study supports the use of the GPTS as a measure of paranoid ideation in French-speaking populations. The GPTS-8 may be preferred to reduce respondent burden. Highlights: We examined the French version of the "Green et al . Paranoid Thoughts Scale" (GPTS). The GPTS can be used as a unidimensional measure of paranoid ideation. We developed a briefer, 8-item version of the GPTS (GPTS-8). The GPTS-8 showed satisfactory psychometric and structural properties. We recommend that the GPTS-8 be used in future research.